2004
DOI: 10.1007/s00421-003-1037-6
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted skin videothermography is a highly sensitive quality tool in the diagnosis and monitoring of complex regional pain syndrome type�I

Abstract: The use of thermography in the diagnosis and evaluation of complex regional pain syndrome type 1 (CRPS1) is based on the presence of temperature asymmetries between the involved area of the extremity and the corresponding area of the uninvolved extremity. The interpretation of thermographic images is, however, subjective and not validated for routine use. The objective of the present study was to develop a sensitive, specific and reproducible arithmetical model as the result of computer-assisted infrared therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 31 publications
0
38
1
1
Order By: Relevance
“…In our study, the highest average ΔT sk recorded in adults was 0.3 °C ( see Table 1 Some studies (Sivanandam et al, 2012;Ring et al,2004;Huygen et al, 2004;Zhu and Xin, 1999;Ben-Eliyahu, 1992) have focused on comparing the thermal profile of healthy people to that of people with an established diagnosis. The ΔT sk in healthy people was found to usually be below 0.5 °C.…”
Section: Contralateral Analysismentioning
confidence: 62%
“…In our study, the highest average ΔT sk recorded in adults was 0.3 °C ( see Table 1 Some studies (Sivanandam et al, 2012;Ring et al,2004;Huygen et al, 2004;Zhu and Xin, 1999;Ben-Eliyahu, 1992) have focused on comparing the thermal profile of healthy people to that of people with an established diagnosis. The ΔT sk in healthy people was found to usually be below 0.5 °C.…”
Section: Contralateral Analysismentioning
confidence: 62%
“…In 1998, Jones recognized the potential use of infrared thermal imaging with regard to skin diseases [16]. But only through the transfer of military technology, HRIT was introduced as a new tool for diagnosis and morbidity assessment, first in race horses and later in humans [17,18]. Since then, HRIT has been used for diverse medical purposes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the interpretation of thermographic images is difficult in patients with very extended and multiple lesions. Third, the interpretation of thermographic images is rather subjective [18]. Forth, since the study was conducted in a resource-poor rural community in Madagascar, it was not possible to standardize thermal measurements as it could have been done in a hospital setting in an industrialized country.…”
Section: Discussionmentioning
confidence: 99%
“…IRT was performed in a room at constant temperatureduring experiments and patients were asked to follow strict instructions before examination. Many studies (Darton & Black 1990;Huygen et al, 2004;Varju et al, 2004;Zaproudina et al, 2009) have shown very good reproducibility of IRT in a temperature-controlled environment. The IRT was reliable to detect osteoarthritis of the knee by the way of distributions of skin temperature.…”
Section: Relationship Between Pain Intensity and The Knee Skin Tempermentioning
confidence: 98%